The contribution of germline rearrangements to the spectrum of BRCA2 mutations. Issue 9 (1st September 2006) - Casilli, F; Tournier, I; Sinilnikova, O M; Coulet, F; Soubrier, F; Houdayer, C; Hardouin, A; Berthet, P; Sobol, H; Bourdon, V; Muller, D; Fricker, J P; et al.
Abstract : Background: Few germline BRCA2 rearrangements have been described compared with the large number of germline rearrangements reported in the BRCA1 gene. However, some BRCA2 rearrangements have been reported in families that included at least one case of male breast cancer. Objective: To estimate the contribution of large genomic rearrangements to the spectrum of BRCA2 defects. Methods: Quantitative multiplex PCR of short fluorescent fragments (QMPSF) was used to screen the BRCA2 gene for germline rearrangements in highly selected families. QMPSF was previously used to detect heterozygous deletions/duplications in many genes including BRCA1 and BRCA2 . Results: We selected a subgroup of 194 high risk families with four or more breast cancers with an average age at diagnosis of ⩽50 years, who were recruited through 14 genetic counselling centres in France and one centre in Switzerland. BRCA2 mutations were detected in 18.6% (36 index cases) and BRCA1 mutations in 12.4% (24 index cases) of these families. Of the 134 BRCA1/2 negative index cases in this subgroup, 120 were screened for large rearrangements of BRCA2 using QMPSF. Novel and distinct BRCA2 deletions were detected in three families and their boundaries were determined. We found that genomic rearrangements represent 7.7% (95% confidence interval 0% to 16%) of the BRCA2 mutation spectrum. Conclusion: The molecular diagnosis of breast cancer predisposition should include screening for BRCA2 rearrangements, at least in families with a high probability of BRCA2 defects.